Chemical engineering. - Harker, J H.; Backhurst, J R.; Richardson, J.F.; Coulson, J.M. ([S.l.] : Butterworth-Heinemann, 1990)
Coulson and Richardson's classic series provides the student with an account of the fundamentals of chemical engineering and constitutes the definitive work on the subject for academics and practitioners. Each book provides clear explanations of theory and thorough coverage of practical applications, supported by numerous worked examples and problems. Thus, the text is designed for students as well as being comprehensive in coverage. A logical progression of chemical engineering concepts, Volume 2 builds on fundamental principles contained in Chemical Engineering Volume 1. Fully up to date and containing descriptions of techniques that are of growing importance in the study of chemical engineering.
Keywords: chemical engineering